Loss-of-Function Mutation in Carotenoid 15,15'-Monooxygenase Identified in a Patient with Hypercarotenemia and Hypovitaminosis A - Lindqvist, Annika; Sharvill, John; Sharvill, Denis E; Andersson, Stefan (The Journal of nutrition, 2007)
The enzyme carotenoid 15,15'-monooxygenase (CMO1) catalyzes the first step in the conversion of dietary provitamin A carotenoids to vitamin A in the small intestine. Plant carotenoids are an important dietary source of vitamin A (retinol) and the sole source of vitamin A for vegetarians. Vitamin A is essential for normal embryonic development as well as normal physiological functions in children and adults. Here, we describe one heterozygous T170M missense mutation in the CMO1 gene in a subject with hypercarotenemia and mild hypovitaminosis A. The replacement of a highly conserved threonine with methionine results in a 90% reduction in enzyme activity when analyzed in vitro using purified recombinant enzymes. The Michaelis-Menten constant (Km) for the mutated enzyme is normal. Ample amounts of carotenoids are present in plasma of persons consuming a normal Western diet, suggesting that the enzyme is saturated with substrate under normal conditions. Therefore, we propose that haploinsufficiency of the CMO1 enzyme may cause symptoms of hypercarotenemia and hypovitaminosis A in individuals consuming a carotenoid-containing and vitamin A-deficient diet.